VOCASIGN: AN INTERACTIVE VOCABULARY LEARNING APPLICATION FOR STUDENTS WITH HEARING DISABILITIES - Siska Nur Rohimah; Chusna Apriyanti; Saptanto Hari Wibawa (English Education Study Program STKIP PGRI Pacitan, 2026)
This study focused on the development and evaluation of VocaSign, an interactive digital tool designed to help students with hearing disabilities master English vocabulary. This study employed a Research and Development (R&D) approach based on the ADDIE model, which consisted of Analysis, Design, Development, Implementation, and Evaluation. The study participants were seventh-grade students with hearing disabilities at SLB YKK Pacitan. Data were collected through interviews, observations, expert validation surveys, student feedback forms, and pre- and post-tests. The findings indicated that VocaSign had high feasibility based on expert evaluation, with an average content validity score of 91.2% and a media validity score of 95.6%, both of which were considered highly feasible. Students responded positively to the implementation of the program. In addition, the average pre-test score increased from 27.5 to 95.0 on the post-test, resulting in an N-gain score of 0.933, which indicated substantial effectiveness. Therefore, VocaSign served as a practical and effective tool for improving English vocabulary proficiency among students with hearing disabilities.